Gender, class, and freedom in modern political theory - Hirschmann, Nancy J. (Princeton University Press, 2008)
In Gender, Class, and Freedom in Modern Political Theory, Nancy Hirschmann demonstrates not merely that modern theories of freedom are susceptible to gender and class analysis but that they must be analyzed in terms of gender and class in order to be understood at all. Through rigorous close readings of major and minor works of Hobbes, Locke, Rousseau, Kant, and Mill, Hirschmann establishes and examines the gender and class foundations of the modern understanding of freedom. Building on a social constructivist model of freedom that she developed in her award-winning book The Subject of Liberty.